Tax Havens, Accounting Experts, and Fee-Setting Rules - Thomas A. Gresik; Kai A. Konrad (Center for Economic Studies and ifo Institute (CESifo), 2017)
Tax havens differ in the specific tax planning arrangements multinational firms can use to reduce their tax liabilities. Given the complexity and cost associated with identifying the most effective tax haven to use, an accounting firm can act as an intermediary between tax havens and multinational corporations. We analyze a model with horizontally differentiated multinationals and tax havens to study the role accounting firm intermediation has on tax haven prices, multinational tax planning choices, accounting firm profits, and tax revenues. In equilibrium, uniform accounting firm fees generate higher accounting firm profit, less tax avoidance, and higher tax revenues than either full price discrimination or haven-specific fees.
Keywords: M41; H26; H73; F38; 330; tax haven; accounting firm; horizontal differentiation; double marginalization; fee-setting rules